Backlash against welfare mothers : past and present - Reese, Ellen, 1969- (University of California Press, 2005)
Ellen Reese considers the politics of welfare in the U.S. from the 1940s to the present, offering a historical perspective on the current debates over 'welfare mothers' & showing how racism has played a large part in the formulation of popular conceptions regarding welfare.